The Position of Women's Heritage Rights in the Context of Islamic Heritage in Indigenous Mandailing in Sipirok District, Tapanuli Selatan Regency - Muhammad Yusuf Siregar; Risdalina Risdalina; Sriono Sriono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze the legal aspects of the Position of Inheritance Rights of Girls in the Context of Islamic Inheritance in Indigenous Mandailing in Sipirok District, South Tapanuli Regency. This research is empirical normative namely research by looking at existing conditions in the field by linking the source of Islamic Law and the legal source of Regulations in force in the Republic of Indonesia. The benefits to be received from the results of this study are to determine the Position of Inheritance of Girls in the Context of Islamic Law and Regulations in Indonesia and the Position of Inheritance of Girls in the Context of Islamic Inheritance in Mandailing Customs in Sipirok District, South Tapanuli Regency, the results of the study stated that In Islamic Inheritance Law strongly recognizes the position of the daughter in receiving inheritance with a strong legal basis in accordance with the al-Qur’an. In Islamic Inheritance Laws, a daughter has a position as Nasabiyah's heir so that she has the right to receive inheritance. In the Mandailing customary inheritance law in Sipirok Mandailing Natal, the position of a daughter is considered as an heir when a male heir is found, but if the girl is a mere woman, the woman is not entitled to inheritance from her parents. The distribution of inheritance in the Mandailing Inheritance law in Sipirok Mandailing Natal uses local customary law, as a basis for the distribution of inheritance which is still being realized in the Community.